THE EFFECTS OF GENOTYPE AND ENVIRONMENT ON SELECTED TRAITS OF OAT GRAIN AND FLOUR. - Czubaszek, Anna (Plant Breeding and Seed Science, 2009)
The purpose of the investigation was to study the effects of variety properties of oat cultivars and environmental conditions on physical traits and chemical composition of grain and flour. Nine oat cultivars had been grown in the experimental plots (stations) located in two experimental stations in Jelenia Góra and Bobrowniki...